Central hexadactylia of the foot: a rare case presentation - Varshney, Prachi; Sudhir Kumar (International Journal of Research in Medical Sciences, 2025)
Polydactyly is congenital duplication type of anomaly of fingers and toes. Its embryogenesis is associated with a disturbance of the anterior-posterior axial development of the limb. Classified in pre-axial, central and post-axial. Classification depends on location of duplication. Details of the case-3 years old, female. Examination findings were single supernumerary toe over metatarsal bone. Extra toe is inclined to transverse arch of foot. Bony structure of supernumerary digit with Y-shaped bifurcation of second metatarsal bone proximal to head of metatarsal. For right upper limb type IV radial club hand. For Left upper Limb-Wassel Type 5 Radial polydactyly. Foramen ovale L to R shunt was also found in 2D Echo. Central polydactyly is a very rare phenotypic presentation. Patient in our case was operated with excision of the supernumerary digit. On dissection, anomalous tendons were found with digital nerve and artery. Tendons were removed, digital nerve incised and digital arteries coagulated. This case is a rare variety. Extra toe dorsally oriented, metatarsal angulated to transverse arch of foot. No metatarsal widening. This case does not fit into the classifications described.